1999
DOI: 10.1079/095442299108728884
|View full text |Cite
|
Sign up to set email alerts
|

Organic acids for performance enhancement in pig diets

Abstract: Organic acids and their salts appear to be potential alternatives to prophylactic in-feed antibiotics and growth promoters in order to improve the performance of weaned piglets, fattening pigs and reproductive sows, although their growth-promoting effects are generally less than that of antibiotics. Based on an analysis of published data, the growth-promoting effect of formates, fumarates and citrates did not differ in weaned piglets. In fattening pigs, formates were the most effective followed by fumarates, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
393
3
36

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(465 citation statements)
references
References 81 publications
(88 reference statements)
13
393
3
36
Order By: Relevance
“…Differences in the diet composition, buffering capacity and farming practices make it difficult to compare results from different studies. However, in general, significant effects on performance and intestinal microbiota were observed in trials with higher than 0.5% inclusion level of FA (Bolduan et al, 1988;Partanen and Mroz, 1999;Canibe et al, 2005;Franco et al, 2005), whereas studies using less than 0.5% FA did not report significant effects (Gabert et al, 1995;Knarreborg et al, 2002). This, together with the observations made in the present investigation, strongly suggest that it is the inhibitory, rather than stimulatory, effect of FA that improves the animal performance.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Differences in the diet composition, buffering capacity and farming practices make it difficult to compare results from different studies. However, in general, significant effects on performance and intestinal microbiota were observed in trials with higher than 0.5% inclusion level of FA (Bolduan et al, 1988;Partanen and Mroz, 1999;Canibe et al, 2005;Franco et al, 2005), whereas studies using less than 0.5% FA did not report significant effects (Gabert et al, 1995;Knarreborg et al, 2002). This, together with the observations made in the present investigation, strongly suggest that it is the inhibitory, rather than stimulatory, effect of FA that improves the animal performance.…”
Section: Discussionsupporting
confidence: 54%
“…It is beyond the scope of this paper to evaluate in detail which microbiota-modulating mode of FA is beneficial for the performance and health, the stimulation of lactic acid fermentation, or general inhibition of bacterial activities in the small intestine of swine. Whichever mode is better for performance, the existence of two opposite outcomes of FA inclusion in feed explains why the results of animal trials testing the effects of FA on animal performance, have been inconclusive (Partanen and Mroz, 1999;Close, 2000;Doyle, 2001;Mroz, 2005). Differences in the diet composition, buffering capacity and farming practices make it difficult to compare results from different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary acidification with organic acids has been shown to improve the growth and feed-to-gain ratio of weaned piglets and growing-finishing pigs, but the mechanisms whereby dietary organic acids enhance pig performance are still poorly understood (Ravindran and Kornegay, 1993;Partanen and Mroz, 1999). Several studies have demonstrated that dietary organic acids improve the ileal apparent digestibility of protein and amino acids in growing-finishing pigs Kemme et al, 1999;Mroz et al, 2000;Partanen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Por sua vez, a adição de ácidos objetiva reduzir o efeito alcalinizante da dieta no estômago, tornando mais efetiva a barreira gástrica que impede/ou dificulta a entrada de microorganismos patogênicos no intestino delgado (TSILOYIANNIS et al, 2001). Tem-se observado que o uso de ácidos orgânicos melhora o desempenho animal e aumenta a digestibilidade ileal de aminoácidos e minerais e o aproveitamento da energia (PARTANEN & MROZ, 1999). Em experimentação in vitro, a utilização de ácidos orgânicos em tecidos da mucosa do cólon de ratos aumentou a absorção de cálcio através do mecanismo de transporte paracelular intestinal (MINEO et al, 2001).…”
Section: Introductionunclassified